Estimation of Fluoride Concentration of Various Citrus and Non-Citrus Fruits Commonly Consumed and Commercially Available in Mathura City - Navin Anand Ingle; Alankrita Chaudhary; B S Goutham; Navpreet Kaur; Rahul Gupta (Wolters Kluwer Medknow Publications, 2013)
Background: Since fluoride is available from various sources, the total ingestion of fluoride by a person should be estimated taking into consideration the fluoride consumed from all the sources including fruits. There are very few epidemiological studies carried out associated with fluoride estimation in fruit samplesand especially in the Indian scenario Objective: To estimate and compare the fluoride concentration of different commercially available citrus and non-citrus fruits in Mathura city. Materials & Method: Fifteen different types of fruits commercially available and consumed by people ofMathura City were collected. Out of the 15 fruit samples 5 were citrus fruits and 10 were non-citrus fruits. The fluoride estimation of fruit samples was done at Central Laboratory,Lucknow. Juices of all 15 fruit samples were prepared, from each sample 10 ml of juice was measured and fluoride testing of each sample was carried out by using Orion 4 star -ion electrode analyzer. The collected data was analyzed using the statistical software program SPSS, version 17. Results: The fluoride concentration in citrus fruits ranged from 0.04ppm (Orange) to 0.08 ppm (Tomato) while in non-citrus fruits it ranged from 0.04ppm (chikoo) to 0.18 ppm (Guava). No significant difference was observed between the mean fluoride concentration of citrus and non citrus fruits. Conclusions: Both citrus and non citrus fruits have fluorides. Guava was found to have the maximumamount of fluoridecontent (0.18 ppm) among both the citrus and non citrus fruits.